Sacubitril/Valsartan Across the Spectrum of Ejection Fraction in Heart Failure. Issue 5 (4th February 2020) - Solomon, Scott D.; Vaduganathan, Muthiah; L. Claggett, Brian; Packer, Milton; Zile, Michael; Swedberg, Karl; Rouleau, Jean; A. Pfeffer, Marc; Desai, Akshay; H. Lund, Lars; Kober, Lars; Anand, Inder; et al.
Abstract : Background: While disease-modifying therapies exist for heart failure (HF) with reduced left ventricular ejection fraction (LVEF), few options are available for patients in the higher range of LVEF (>40%). Sacubitril/valsartan has been compared with a renin-angiotensin-aldosterone–system inhibitor alone in 2 similarly designed clinical trials of patients with reduced and preserved LVEF, permitting examination of its effects across the full spectrum of LVEF. Methods: We combined data from PARADIGM-HF (LVEF eligibility⩽40%; n=8399) and PARAGON-HF (LVEF eligibility≥45%; n=4796) in a prespecified pooled analysis. We divided randomized patients into LVEF categories: ⩽22.5% (n=1269), >22.5% to 32.5% (n=3987), >32.5% to 42.5% (n=3143), > 42.5% to 52.5% (n=1427), > 52.5% to 62.5% (n=2166), and >62.5% (n=1202). We assessed time to first cardiovascular death and HF hospitalization, its components, and total heart failure hospitlizations, all-cause mortality, and noncardiovascular mortality. Incidence rates and treatment effects were examined across categories of LVEF. Results: Among 13 195 randomized patients, we observed lower rates of cardiovascular death and HF hospitalization, but similar rates of noncardiovascular death, among patients in the highest versus the lowest groups. Overall sacubitril/valsartan was superior to renin-angiotensin-aldosterone–system inhibition for first cardiovascular death or heart failure hospitalization (Hazard Ratio [HR] 0.84 [95% CI, 0.78–0.90]), cardiovascular death (HR 0.84 [95% CI, 0.76–0.92]), heart failure hospitalization (HR 0.84 [95% CI, 0.77–0.91]), and all-cause mortality (HR 0.88 [95% CI, 0.81–0.96]). The effect of sacubitril/valsartan was modified by LVEF (treatment-by-continuous LVEF interaction P =0.02), and benefit appeared to be present for individuals with EF primarily below the normal range, although the treatment benefit for cardiovascular death diminished at a lower ejection fraction. We observed effect modification by LVEF on the efficacy of sacubitril/valsartan in both men and women with respect to composite total HF hospitalizations and cardiovascular death, although women derived benefit to higher ejection fractions. Conclusions: The therapeutic effects of sacubitril/valsartan, compared with a renin-angiotensin-aldosterone–system inhibitor alone, vary by LVEF with treatment benefits, particularly for heart failure hospitalization, that appear to extend to patients with heart failure and mildly reduced ejection fraction. These therapeutic benefits appeared to extend to a higher LVEF range in women compared with men. Clinical Trial Registration: https://www.clinicaltrials.gov . Unique identifiers: NCT01920711 (PARAGON-HF), NCT01035255 (PARADIGM-HF). Abstract : Supplemental Digital Content is available in the text.